Utilização de água produzida do petróleo na produção e capacidade de fitoextração de cactácea no semiárido brasileiro - Costa, Danniely de Oliveira (2019)
Fresh water is an essential resource for the full functioning and development of plants; however, is becoming increasingly scarce. The reutilization of wastewater in the production of forage species appears as an important alternative water source, especially in regions characterized by high water scarcity and climatic adversities, as is the case of the Brazilian semi-arid region. The objective of the present study was to analyze the effects of dilutions of treated water treated on forage palm (Nopalea cochenillifera (L.) Salm-Dick) and soil physical-chemical characteristics. For this, an experimental area was set up in a greenhouse, in the Department of Agrarian and Forestry Sciences of the Agricultural Science Center of the Universidade Federal Rural do Semi-Árido (UFERSA). The experiment was carried out in randomized blocks (DBC) with five treatments and five replications. The treatments evaluated were T1 - 100% of underground water (UW), T2 - 75% of UW and 25% of treated produced water treated (PW), T3 - 50% of UW and 50% of PW, T4 - 25% of UW and 75% PW and T5 - 100% PW. For the implantation of the experiment 20 L pots filled with gravel (No. 1) were used covering the base, and with soil (Argisol) of the Rafael Fernandes Experimental Farm, in Mossoró. During the experimental period, the physico-chemical characterization of treated water from an oil field and groundwater was carried out. After 240 days after planting (DAP) were evaluated the chemical characteristics of the soil. For the productivity, agronomic characteristics, accumulation of nutrients in cladodes and roots, translocation factors and bioaccumulation, the effects of the treatments were analyzed. The data were submitted to analysis of variance, mean tests and orthogonal contrasts, using the Sisvar statistical software 5.6 (System for Analysis of Variance). Cultivation of forage palm irrigated with treated treated water proved viable. The contents of Na+, Cl-, CO3 - and HCO3 2- found in the treated produced water dilutions may limit the use of such water for irrigation purposes. In relation to the physical-chemical attributes, the values of Na+, Ca2+, Mg2+, PST, Cr and Pb were influenced significantly by water treated applications diluted produced; however, there was a significant increase with the dilutions only for Mg2+, Cr and Pb contents. The application of treated water promoted increase of Ca, Fe, Cu, Cr, Ni and Cd levels in cladodes and of K, Mg, Mn, Zn, Pb, Cd and Ni in roots of forage palm, when compared T1 and T5 treatment. The T3 treatment promoted plant height and thickness of the upper cladodes, as well as increases in green matter and dry matter production, showing that the applied dose of 50% of the produced water can meet the crop needs satisfactorily. The forage palm presented efficiency in the translocation of the elements K, Ca, Mg, Mn, Zn, Ni, Cd and Pb from the root to the aerial part, and in the bioaccumulation of all the nutrients analyzed in their tissues (roots and cladodes), accumulation of K, Fe, Mn and Cu more expressive when compared to the others